Healing Trauma of Sexual Abuse and Rejecting Patriarchal Authority in Gail Anderson-Dargatz’s The Cure for Death by Lightning - Abdullah, Md Abu Shahid (Literary Studies, 2025)
Dealing with Gail Anderson-Dargatz’s The Cure for Death by Lightning the article aims to show that Maud’s scrapbook and Beth’s autobiography depict a family history of sexual violence and serve as main means of healing for both mother and daughter respectively. The article also aims to demonstrate that instead of becoming a vehicle for communication, the scrapbook detaches Beth from the female community of her mother and the spirit of her grandmother. The scrapbook thus represses its trauma and at the same time turns them into expression; it also encodes and hides a cycle of sexual abuse by male family members. The paper further aims to show that in the novel, both traumatic realism and magical realism converge in Beth’s lightning arm as a technique of voicing and healing her trauma. The paper again emphasises the role of Coyote figure behind Beth’s rewriting her trauma, arguing that Beth’s trauma of sexual abuse, which she cannot utter and which Maud refuses to listen to, is expressed through the Native Coyote figure where Coyote is associated with the dichotomy between female victims and male victimisers. Finally, the article connects the lesbian relationship of Beth and her Native friend, Nora, and the bodily grotesque of different female characters with female agency and independence.